Peningkatan Kompetensi Guru: Pelatihan Keterampilan Abacus Bagi Guru Madrasah Ibtidaiyah Negeri Kota Bandar Lampung - Siti Patimah; Abdul Latief Arung Arafah; Deti Elice; Fahrina Yustiasari Liriwati; Armizi Armizi (Lembaga Pengembangan Kinerja Dosen, 2024)
Abacus skills training has been identified as an effective method for improving students' basic mathematics abilities and mental calculation skills. This article discusses the implementation of Abacus skills training for teachers at Madrasah Ibtidaiyah Negeri (MIN) Bandar Lampung City with the aim of improving the quality of basic mathematics teaching. In the context of MIN, this training is considered relevant to develop teachers' potential in teaching mathematics and improve students' ability to understand mathematical concepts better. This article also describes the steps for implementing Abacus skills training at MIN and its benefits in improving the quality of mathematics learning at this Islamic educational institution